Clinico-epidemiological profile and diagnostic procedures of tuberculosis in children: a study from OPD of Bangabandhu Sheikh Mujib Medical University - Haque, Mujammel; Ali, M. Asif; Ferdosh, Taslima; Talukder, Manik Kumar (International Journal of Contemporary Pediatrics, 2025)
Background: Childhood tuberculosis (TB) is a significant cause of mortality and morbidity, contributing to a considerable TB burden in developing countries like Bangladesh. The aim of this study was to describe the clinical profile and diagnostic procedures in childhood TB cases in the outpatient department (OPD) of a tertiary care hospital. Methods: This cross-sectional study was conducted on children aged 3 months to 18 years from July 2023 to June 2024 in the OPD of the Paediatrics Department at Bangabandhu Sheikh Mujib Medical University (BSMMU) who were diagnosed with tuberculosis according to the National Guidelines for the Management of Tuberculosis in Children, 2021. Data were collected through direct interviews and analyzed by MS Excel. Results: Among 834 suspected patients, 139 were diagnosed with tuberculosis. Here, 47.48% cases were pulmonary TB and 52.51% were extrapulmonary TB (EPTB). Among EPTB 30.93% were TB lymphadenitis. Common symptoms like fever were present in 84.48%, weight loss in 69.78%, cough in 64.74% and lumps in the neck and axilla in 35.25% cases. Mantoux test was positive in 71.92%, abnormal chest X-ray findings in 46.76%. Fine needle aspiration cytology from lymph nodes was suggestive in 32.37%. Sputum GeneXpert and stool GeneXpert ultra tests were positive in 10.79% and 20.14% respectively. Conclusion: This study found that cases of extrapulmonary TB were more prevalent than pulmonary TB among children. The diagnosis of tuberculosis was primarily based on clinical suspicion, supported by various investigations, especially bacteriological detection through stool and sputum GeneXpert ultra tests in children.